Smart Tourist Destinations, a new conceptual contribution for local development in Ecuador. Case of "Portoviejo Creative City UNESCO" (Research, Society and Development, 2021)
Tourism activity becomes more competitive every day, the exponential growth of technology makes it possible to improve communications between businesses and final customers, the emergence of new applications makes it easier for tourists to acquire services. For this and many other things, the public administration in tourist developed countries such as Spain is committed to the certification of Smart Tourist Destinations (STD) with criteria related to accessibility, sustainability, governance, technology and innovation. This literature review uses basic content analysis tools to classify the information from documents, manuals and specialized articles in various databases, which seeks to raise the foundations that serve as a reference for new tourism studies focused on this field. novel for Ecuador, but not so much around the world. Portoviejo is a city recently declared as a Creative City by UNESCO, and it seeks to promote a new model of tourism management, which makes use of its cultural heritage, led by gastronomic diversity, and in turn be able to promote this development with the evolution towards a smart destination.